Effect of Sowing Season, Age and Height of Cutting of the Primary Crop of Sorghum bicolor cv. ‘Abu Sabeen’ on Growth and Forage Yield of the Secondary Crop (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted for two consecutive seasonsat the Gezira Research Farm to study the effect of growing season, ageand height of cutting of the primary crop of ‘Abu Sabeen’, on theregrowth yield. The first experiment was sown on 4th of September 2005and the second was on 7th of June 2006.The treatments comprised cuttingthe primary crop at 5 ages i.e. 6, 7, 8, 9 and 10 weeks from sowing and 4cutting heights i.e. 5, 10, 15 and 20 cm above ground. The 20 treatmentswere allotted to a randomized complete block design with 3 replications.Data were collected on weather conditions, forage yield, plant height, andculm density of the first regrowth. The growing season was crucial formultiple -cut crop of ‘Abu Sabeen’; long days and high temperature beingmore conducive for high dry matter yield of the regrowth mainly throughthe increase in plant height, and shorter days and relatively lowertemperature being conducive for high culm density and retarded growth.Taller plants were determinant of the regrowth yield than the increase inthe culm density. Highest dry matter yields of the regrowth wereassociated with June sowing and cutting the primary crop at the age of 7weeks and cutting height of 15 or 20 cm above ground.